Pengaruh Dukungan Organisasi dan Kepuasan Kerja terhadap Kinerja Dosen di Universitas Gorontalo - Darman, Darman (Patria Artha Management Journal, 2017)
ABSTRACT  This research aims to: (a) analyze the effects of organizational support on lecturers’ job performances, (b) analyze the effects of job satisfaction on lecturers’job performances and (c) analyze the effect simultaneously between of Organizational Support and job satisfaction on lecturers’ job performance. This was a quantitative research. The population of this research is 100 lecturers in Gorontalo University. The sample, consisting of 47 lecturers, was taken from the population by means of a Non Probablity sampling technique. The data were tested for their validity and reliability.The data were analyzed employing multi regressions. The calculation on the data employed the SPSS Program for Windows. The simple regression showed that organizational support and jobsatisfactionpositively and not significantly affected thejob performances of fixedlecturers in Gorontalo University, with standardized coefficients beta of 0,246 and 0,216 respectively. The multiple regressions showed that the simultaneously betweenorganizational support and job satisfaction positively and significantly affected the job performances of fixed lecturers in Gorontalo University, with a coefficient of determination of 17,80%. It can then be concluded that organizational support and job satisfaction reallypositively and significantly affect the job performances of lecturers in Gorontalo University.  Keywords : Organizational support;job satisfaction ; lecturers;job performance